The effect of using a variety of teaching methods in teaching the transmission skills from above and below in volleyball (Journal of the College of Basic Education, 2022)
Through the researchers' meeting with teachers and specialists in physical education, they noticed that many physical education teachers do not use modern methods in teaching physical education, including the game of volleyball, which negatively led to a delay in the level of students in this game.Among the modern methods that Mostin mentioned is directness, and this we did not find in teaching those whom we saw and asked about these methods. If one of the special methods of Mustin is used, it is used alone, as the problem is embodied in the lack of diversity in the methods of teaching the skill to students, and this is what the researchers will seek, that is, we use more From a method in teaching the skill of sending in volleyball